Routine Stock Opname in Enhancing Service of Halodoc's Order and Increasing Transactions - I Nyoman Arya Purnata Megantara; Titien Siwi Hartayu (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2025)
In partnering with the e-commerce platform Halodoc, one of the challenges encountered is unfulfilled orders due to discrepancies between the system's stock and conventional stock. Therefore, the researcher aims to determine whether maintaining drug availability through routine stock opname in an online (e-commerce) setting can also enhance service quality. This study is quasi-experimental research conducted at Manut Farma Pharmacy from July to September 2023. The research involves daily routine stock opname of 312 registered drug items on the Halodoc application. These 312 drug items met the inclusion criteria, which were "Drugs included in the list of drugs available in the pharmacy and registered in the Halodoc program," and the exclusion criterion of "Physical stock of drugs having an expiration date of not less than 6 months." The research findings indicate that almost all incoming Halodoc orders can be served effectively (86%), which represents a significant increase of 19% (A sig. 0.003; p=0.05) compared to the previous three months (67%). The product is one of the key aspects of marketing, and by maintaining up-to-date stock conditions, it directly affects the fulfillment of incoming drug orders by enhancing the serving process. Routine stock opname can help improve the service of Halodoc orders, Although the number of incoming orders for Halodoc transactions is still relatively low, on the other hand, routine stock checks have also contributed to a 10% increase in conventional transactions.